Preparation and application of modified nano zero-valent iron material

By using amino-modified silicon-based materials to load nano zero-valent iron composites in uranium mining and smelting wastewater treatment, the problems of low active site density and insufficient selectivity in uranium mining and smelting wastewater treatment are solved, and efficient and stable uranium removal effect is achieved.

CN120361866APending Publication Date: 2025-07-25NANHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510505558.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-21
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

Traditional nano zero-valent iron materials have problems such as low active site density, significant self-passivation oxidation tendency, and insufficient selective adsorption capacity in uranium mining and smelting wastewater treatment, resulting in low treatment efficiency and risk of secondary pollution.

Method used

The composite material with amino-modified silicon-based materials loaded with nano zero-valent iron is used to disperse the loaded nano zero-valent iron in the pores of the silicon-based materials, increase the specific surface area and provide more active sites. At the same time, the selective adsorption and reduction effects of uranium are enhanced by utilizing the selective adsorption and reduction effects of uranium.

Benefits of technology

The removal rate of uranium is significantly improved, with an average removal rate of 97.56%. The stability of solid uranium products is good, the desorption rate of uranium is reduced, the selective removal ability of uranium is enhanced, and the problem of easy agglomeration of nano zero-valent iron is overcome.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120361866A_ABST
    Figure CN120361866A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of modified nanoscale zero-valent iron and application of the modified nanoscale zero-valent iron to uranium removal in uranium mining and metallurgy wastewater, and belongs to the field of heavy metal pollution remediation. According to the method, nano zero-valent iron is loaded on an amino modified silicon-based material, so that the problems that traditional nano zero-valent iron is easy to oxidize and agglomerate and poor in selectivity are solved. Wherein the modified nano zero-valent iron material comprises nano zero-valent iron and an amino modified silicon-based carrier. The preparation method comprises the following steps: S1, soaking a silicon-based material in absolute ethyl alcohol, adding a modifier, grafting to the silicon-based material, stirring, performing ultrasonic treatment, washing and drying to obtain an amino-modified silicon-based material; s2, preparing a Fe < 3 + > solution, adding the amino-modified silicon-based material, stirring, performing ultrasonic treatment, washing, and performing freeze drying to obtain a precursor; and S3, soaking the precursor obtained in the step S2 in a solvent, dropwise adding a reducing agent in an inert gas atmosphere, carrying out stirring reaction, separating particulate matters, washing, and carrying out vacuum drying to obtain the modified nano zero-valent iron material. The prepared modified nano zero-valent iron material is good in stability, capable of efficiently treating uranium mining and metallurgy wastewater, simple in process and low in cost, and has industrial application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of heavy metal pollution remediation. Specifically, it particularly relates to a preparation method of nano zero-valent iron supported on amino-modified silicon-based materials and its application in the treatment of uranium pollution in industrial wastewater from uranium mining and smelting. Background Art

[0002] A large amount of mine pit water inrush and underground leachate, leachate generated from ore heap leaching or in-situ leaching, wastewater from hydrometallurgical processes, and leachate from waste rock dumps and tailing ponds containing radioactive nuclides and heavy metals are generated in the processes of uranium mining, leaching, and hydrometallurgical processing.

[0003] The uranium-containing wastewater without passivation treatment exhibits a significant synergistic mechanism of chemical toxicity coordination effect and internal irradiation risk of radioactive nuclides. Both of them can pose health hazards to the human body, and there are serious potential risks for long-term exposure at low doses or high-dose exposure.

[0004] Traditional treatment methods (such as neutralization precipitation, adsorption, and ion exchange) have problems such as low efficiency, large amount of sludge, and high risk of secondary pollution, especially poor removal effects on low-concentration uranium and composite pollution. Compared with traditional methods, nZVI has advantages such as high efficiency, multi-mechanism synergy, and strong anti-interference in uranium pollution remediation, and is especially suitable for the treatment of uranium mining and metallurgy wastewater, polluted soil, and groundwater.

[0005] The nano zero-valent iron system shows a significant self-passivation oxidation tendency in environmental media. A FeOOH / Fe3O4 passivation layer will spontaneously form on the surface, leading to an increase in the interfacial electron transfer impedance; the spontaneous aggregation effect at the nanoscale results in the attenuation of the effective active specific surface area; the lack of specific surface chelating groups leads to insufficient coordination recognition ability for uranyl ions.

[0006] Therefore, it is necessary to design a material that can remove or reduce the limitations of traditional nano zero-valent iron materials to solve the above technical problems. Summary of the Invention

[0007] Aiming at the problems of low density of active sites, significant self-passivation oxidation tendency, and insufficient selective adsorption ability of traditional nano zero-valent iron materials in the treatment of uranium-containing wastewater, the present invention proposes a preparation method and application of a nano zero-valent iron composite material supported on amino-modified silicon-based materials.

[0008] To achieve the above object, the technical solution adopted by the present invention includes the following steps:

[0009] A modified nano-zero-valent iron material, comprising: nano-zero-valent iron and an amino-modified silicon-based material; the nano-zero-valent iron is loaded within the amino-modified silicon-based material; by utilizing the cavities on the surface and the internal pores of the silicon-based material, the nano-zero-valent iron is dispersed and loaded inside the pores of the silicon-based material, reducing the agglomeration of the nano-zero-valent iron, increasing the specific surface area, and providing more active sites; at the same time, the amino-modified silicon-based material has selective adsorption for uranium, further enhancing the adsorption, reduction, and coprecipitation effects of the nano-zero-valent iron with uranium, and accelerating the removal of uranium by the nano-zero-valent iron; at the same time, the iron-uranium deposits after the reaction will be fixed inside the pores, thereby restricting the transformation and migration of uranium.

[0010] Preferably, the preparation method of the amino-modified silicon-based material is: Step S1, soaking the silicon-based material in absolute ethanol, adding a modifier to graft onto the silicon-based material, stirring, ultrasonicating, washing, and drying to obtain the amino-modified silicon-based material.

[0011] Preferably, the modifier is APTES, VTES, ammonium persulfate, etc.

[0012] Preferably, the stirring speed is 600 - 1000 rpm.

[0013] Preferably, the soaking time is 10 - 12 hours.

[0014] Preferably, the ultrasonic condition is ultrasonicating at room temperature for 10 - 30 min.

[0015] Preferably, the mass ratio of the silicon-based material to the modifier is 1:(0.2 - 1).

[0016] Preferably, the washing is washing with ultrapure water until neutral.

[0017] Preferably, the drying temperature is 80 - 110 °C.

[0018] Preferably, the preparation method of the nano-zero-valent iron material is: Step S2, preparing an Fe 3+ solution, adding the amino-modified silicon-based material, stirring, ultrasonicating, washing, and freeze-drying to obtain a precursor; Step S3, soaking the precursor in cyclohexane, dropping a reducing agent, stirring, separating the particulate matter, washing, and vacuum-drying to obtain the modified nano-zero-valent iron material.

[0019] Preferably, the Fe 3+ solution is prepared from ferric chloride hexahydrate.

[0020] Preferably, the stirring condition is 600 - 800 rpm.

[0021] Preferably, the soaking time is 15 - 20 min.

[0022] Preferably, the dropping rate of the reducing agent is 3 mL / min.

[0023] Preferably, the separation is to attract and isolate the solid particulate matter from the bottom using a magnet.

[0024] Preferably, the washing is to alternately use deoxygenated ultrapure water and deoxygenated ethanol twice each.

[0025] The application of the above-mentioned amino-modified silicon-based material supported nano zero-valent iron composite material in the treatment of uranium mining and metallurgy wastewater.

[0026] Furthermore, in the said application, the amino-modified silicon-based material supported nano zero-valent iron composite material is added to the wastewater containing pollutants for reaction, and the dosage of the amino-modified silicon-based material supported nano zero-valent iron composite material is 0.1 - 3 g / L.

[0027] Furthermore, the pollutant is heavy metal uranium (VI).

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention provides a preparation method of modified nano zero-valent iron and its application in uranium removal from uranium mining and metallurgy wastewater, including the following steps: soaking the silicon-based material in absolute ethanol, adding a modifier to graft onto the silicon-based material, stirring, ultrasonicating, washing and drying to obtain the amino-modified silicon-based material. The preparation method of the modified nano zero-valent iron is: preparing an Fe 3+ solution, adding the amino-modified silicon-based material, stirring, ultrasonicating, washing, and freeze-drying to obtain a precursor. Soaking the precursor in cyclohexane, dropping a reducing agent, stirring, separating the particulate matter, washing, and vacuum drying to obtain the modified nano zero-valent iron material. The average uranium removal rate of this material reaches 97.56%, which is superior to that of the traditional nano zero-valent iron under the same conditions. The uranium-fixing product has good stability, and the uranium desorption rate is only 0.65% after soaking in acid solution for 30 days. The uranium removal rate of this material changes very little in wastewater with different impurity ion strengths, and it has the ability to selectively remove uranium. Compared with nano zero-valent iron, the specific surface area is increased, there are more active sites, the selectivity for uranium is enhanced, thus enhancing the uranium removal ability of the composite material, and at the same time overcoming the problem of easy agglomeration of nano zero-valent iron. Description of the Drawings

[0030] Figure 1 It is the flow chart of the preparation of the material of the present invention.

[0031] Figure 2 It is the scanning electron microscope image of the amino-modified silicon-based material supported nano zero-valent iron composite material in the present invention.

[0032] Figure 3 It is the test effect of the amino-modified silicon-based material supported nano zero-valent iron composite material on uranium under different factors. Detailed Embodiments

[0033] The following provides a detailed description of the specific embodiments of the present invention. It should be understood that the specific embodiments described herein are only for the purpose of illustrating and explaining the present invention, and are not intended to limit the present invention.

[0034] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.

[0035] Example 1

[0036] Comparison of the Preparation of Nano-Zero-Valent Iron before and after Amino-Modified Silicon-Based Materials and Its Effect on Uranium Removal

[0037] Weigh 1 g of silicon-based material powder and mix it evenly with 50 mL of absolute ethanol. Then add 2.5 mL of APTES to it and stir magnetically at 40 °C for 12 hours. After drying at 80 °C, the amino-modified silicon-based material is obtained. Subsequently, add the above-mentioned silicon-based material powder and 6.77 g of ferric chloride hexahydrate to 50 mL of cyclohexane and mix evenly. After heating and reacting at 40 °C for 10 hours, dry at 80 °C to obtain the precursor. Then keep it in a nitrogen atmosphere for 2 hours. Add 50 mL of cyclohexane to a beaker and add the precursor. Then slowly and uniformly dropwise add the sodium borohydride solution and stir magnetically at 40 °C for 30 min. After washing and vacuum drying, the amino-modified silicon-based material supported nano-zero-valent iron (SGB-NH2@nZVI) is obtained.

[0038] Control Experiment 1: Under a nitrogen atmosphere, weigh 6.77 g of ferric chloride hexahydrate and add it to a flask containing 50 mL of cyclohexane. Then slowly and uniformly dropwise add the sodium borohydride solution and stir magnetically at 40 °C for 30 min. After washing and vacuum drying, nano-zero-valent iron is obtained.

[0039] Perform different characterization analyses on the obtained composite materials. As Figure 2 shown, compared with nano-zero-valent iron, the surface of the amino-modified silicon-based material supported nano-zero-valent iron (SGB-NH2@nZVI) presents smooth granular shapes and less agglomeration phenomena. The particle size is in the nanoscale, indicating that the obtained composite material is a nanomaterial. After being supported by the amino-modified silicon-based material, the surface of the material presents nanosheet-like substances with a size of nanosheets. This indicates the successful preparation of the amino-modified silicon-based material supported nano-zero-valent iron composite material.

[0040] Example 2

[0041] Comparison of the Preparation of Nano-Zero-Valent Iron before and after Amino-Modified Silicon-Based Materials and Its Effect on Uranium Removal

[0042] Weigh 1 g of silicon-based material powder and mix it evenly with 50 mL of absolute ethanol. Then add 2.5 mL of APTES to it and heat and react at 40 °C for 12 hours under a magnetic stirrer. After that, dry it at 80 °C in a blast drying oven to obtain the amino-modified silicon-based material. Subsequently, add the above silicon-based material powder and 1.244 g of ferric chloride hexahydrate to 50 mL of cyclohexane and mix them evenly. Then heat and react at 40 °C for 10 hours under a magnetic stirrer. After drying at 80 °C in a blast drying oven, a precursor is obtained. Then keep it in a nitrogen atmosphere for 2 hours. Add the precursor to 50 mL of cyclohexane, and slowly and evenly dropwise add sodium borohydride. After heating and reacting at 40 °C for 30 min under a magnetic stirrer, through washing and vacuum drying, the amino-modified silicon-based material supported nano zero-valent iron (SGB-NH2@nZVI) is obtained.

[0043] Characterize and analyze it. Due to the change in the ratio of iron / silicon-based material, measure the specific surface area of the composite material before and after modification of materials with different ratio amounts. When the mass ratio of iron / silicon-based material is 0.43, the BET specific surface area of the composite material increases from 387.46 m 2 / g before modification to 504.41 m 2 / g. When the mass ratio of iron / silicon-based material continues to increase to 2.33, the BET specific surface area of SGB-NH2@nZVI is 596.32 m 2 / g. Compared with the unmodified composite material, the specific surface area increases by 1.5 times. With the increase in the mass ratio of iron / silicon-based material, compared with the unmodified composite material, the amino-modified silicon-based material loading significantly improves the specific surface area of the composite material. The increase in the specific surface area indicates that its adsorption of pollutants will be enhanced, which is beneficial to the adsorption of pollutants on the surface of the composite material and enhances the removal of pollutants.

[0044] Example 3

[0045] Preparation of nano zero-valent iron before and after amino-modified silicon-based material and comparison of its uranium removal effect

[0046] Add 10 mg of amino-modified silica supported material particles to a 50 mL conical flask containing a uranium solution with a concentration of 8 mg / L. Adjust the initial pH to 5. After 120 min of reaction, the uranium removal rate reaches as high as 97.59%. Conduct desorption and leaching experiments on the uranium-fixed sediment. The average leaching rate of acid solution immersion does not exceed 0.81%.

[0047] Control experiment 1

[0048] 10 mg of the amino-modified silica-supported material particles were added to a 50 mL conical flask containing a uranium solution with a concentration of 10 mg / L. The initial pH was adjusted to 5. After 120 min of reaction, the uranium removal rate reached as high as 97.51%. Desorption and leaching experiments were carried out on the uranium-loaded sediment. The average leaching rate by acid solution immersion was no more than 0.81%.

[0049] The composite material obtained in this example was used for the removal of uranium in uranium mining and metallurgy wastewater. Among them, the dosage of the composite material was 10 mg, and the concentration of U(VI) was 10 mg / L. The results are as Figure 3 (a) shown. The SGB-NH2@nZVI composite material had the best removal effect on U(VI) within 20 min. Sampling and determination were carried out at different pH points, and the results are as Figure 3 (b) shown. The SGB-NH2@nZVI composite material had the best removal effect on U(VI) under the condition of pH = 5. All the above results of U(VI) removal can show that the loading of the amino-modified silicon-based material can greatly improve the ability of the composite material to remove pollutants.

[0050] The present invention preferably separates and fixes uranium in uranium mining and metallurgy wastewater. The present invention has no special limitation on the specific method for recovering uranium, and the methods well-known to those skilled in the art can be used.

[0051] The materials provided by the present invention were described in detail with the above combined examples, but they cannot be understood as limiting the protection scope of the present invention.

[0052] The above is only the preferred experimental scheme of the present invention, and it does not make any form of limitation to the present invention. It should be pointed out that for those of ordinary skill in the art in this technical field, without departing from the experimental principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.

Claims

1. A preparation method of a modified nano zero-valent iron material, comprising nano zero-valent iron and an amino-modified silicon-based material, wherein the nano zero-valent iron is loaded inside the pores of the silicon-based material; the nano zero-valent iron is obtained by reducing an Fe 3+ solution; the mass ratio of the dosage of the amino-modified silicon-based material to the Fe 3+ solution is 1:(0.2-1).

2. The modified nano zero-valent iron material according to claim 1, wherein The preparation method of the amino-modified silicon-based material is as follows: Immerse the silicon-based material in absolute ethanol, add a modifier to graft it onto the silicon-based material, stir, ultrasonicate, wash, and dry to obtain the amino-modified silicon-based material.

3. The method according to claim 2, wherein The modifier includes, but is not limited to, APTES (3-aminopropyltriethoxysilane), VTES (vinyltriethoxysilane), ammonium persulfate, etc.

4. The modified nano zero-valent iron material according to claim 2, characterized in that, The immersion time is 10 to 12 hours; the washing is with deoxygenated ultrapure water until neutral; the drying temperature is 80 to 110 °C; the ultrasonication condition is ultrasonication at room temperature for 10 to 30 min; the stirring condition is stirring at 600 to 1000 rpm for 10 to 12 hours.

5. The modified nano zero-valent iron material according to claim 1, wherein The preparation method of the modified nano zero-valent iron material is as follows: Prepare an Fe 3+ solution, add an amino-modified silicon-based material, stir, sonicate, wash, freeze-dry to obtain a precursor; soak the precursor in a solvent, dropwise add a reducing agent, stir, separate the particulate matter, wash, and vacuum dry to obtain the modified nano zero-valent iron material.

6. The modified nano zero-valent iron material according to claim 5, characterized in that, The dropping rate of the reducing agent is 3 mL / min, the stirring condition is stirring at 600 to 800 rpm for 15 to 20 min; the separation is to attract and separate the solid particles using a magnet; the washing is to wash alternately with deoxygenated ultrapure water and deoxygenated ethanol twice each; the vacuum condition is 2.0 kPa or less.

7. The method according to claim 5, wherein The reducing agent includes, but is not limited to, sodium borohydride, potassium borohydride, hydrazine hydrate solution; the whole reaction process is protected by an inert environmental atmosphere.

8. Application of modified nano zero-valent iron, characterized in that, Put the modified nano zero-valent iron of claim 1 into uranium mining and metallurgy wastewater to reduce or adsorb the radioactive element uranium.